1998
DOI: 10.1097/00005768-199802000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dehydration on isometric muscular strength and endurance

Abstract: To examine the effects of rapid dehydration on isometric muscular strength and endurance, seven men were tested at baseline (control) and after a dehydration (dHST) and a euhydration (eHST) heat stress trial. The dHST consisted of intermittent sauna exposure until 4% of body mass was lost, whereas the eHST consisted of intermittent sauna exposure (same duration as dHST) with water replacement. Peak torque was determined for the knee extensors and elbow flexors during three isometric maximal voluntary contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 12 publications
1
47
2
1
Order By: Relevance
“…The strenuous nature of the resistance protocol prompted one dropout and necessitated highly Wt participants. Therefore, this study more precisely replicated the demands of ecologically common resistance exercise protocols (i.e., session duration, multiple muscle groups, and repeated lifts) than much of the previous literature which has focused on maximal force production during single bouts of resistance exercise (Bosco et al 1968(Bosco et al , 1974Evetovich et al 2002;Ftaiti et al 2001;Greiwe et al 1998;Houston et al 1981;Montain et al 1998;Saltin 1964;Serfass et al 1984;Viitasalo et al 1987). Total repetitions for all exercises and total repetitions within each of the six exercises were signiWcantly lower for DEHY versus HE, indicating dehydration (»3%) impaired resistance exercise performance.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The strenuous nature of the resistance protocol prompted one dropout and necessitated highly Wt participants. Therefore, this study more precisely replicated the demands of ecologically common resistance exercise protocols (i.e., session duration, multiple muscle groups, and repeated lifts) than much of the previous literature which has focused on maximal force production during single bouts of resistance exercise (Bosco et al 1968(Bosco et al , 1974Evetovich et al 2002;Ftaiti et al 2001;Greiwe et al 1998;Houston et al 1981;Montain et al 1998;Saltin 1964;Serfass et al 1984;Viitasalo et al 1987). Total repetitions for all exercises and total repetitions within each of the six exercises were signiWcantly lower for DEHY versus HE, indicating dehydration (»3%) impaired resistance exercise performance.…”
Section: Discussionmentioning
confidence: 59%
“…Studies measuring dehydration eVects on muscular strength or anaerobic performance are sparse and have yielded mixed results, showing signiWcant impairment (Bigard et al 2001;Bosco et al 1968Bosco et al , 1974Ftaiti et al 2001;Greenleaf et al 1967;Houston et al 1981;Judelson et al 2007b;SchoVstall et al 2001;Viitasalo et al 1987;Yoshida et al 2002), no eVects (Cheuvront et al 2006;Evetovich et al 2002;Greiwe et al 1998;Judelson et al 2007b; Montain et al 1998;Saltin 1964;Serfass et al 1984;Singer and Weiss 1968;Yoshida et al 2002) or even signiWcant improvements (Ahlman and Karvonen 1961;Widerman and Hagan 1982). Studies examining muscular endurance have shown signiWcant impairment (Bosco et al 1974;Caterisano et al 1988;Montain et al 1998;Torranin et al 1979) and no diVerence (Caterisano et al 1988;Ftaiti et al 2001;Greiwe et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, skinfold measurement requires trained personnel and may not be as accurate for individuals with obesity. 28, 29,52 In addition, there are racial and ethnic differences in the location of body mass storage and fat deposition that affect skin fold measurements. 53,54 Hydrostatic (underwater) weight and air displacement plethysmography are simple to perform but require expensive equipment; both methods may underestimate body fat percentage in extremely lean athletes.…”
Section: National Sport Governing Bodies Address Rapid Weight Loss Atmentioning
confidence: 99%
“…However, for a given person and event, the greater the dehydration level (after achieving the threshold for performance degradation) the greater the performance decrement. Dehydration probably does not alter muscle strength, 56 but sometimes has been reported to reduce dynamic small muscle endurance. 57,58 In addition, dehydration of over 2% often adversely influences cognitive function in the heat; however, this area requires more research.…”
Section: Hypohydrationmentioning
confidence: 99%